Insights into diagnostic difficulties in spinal muscular atrophy: a Case Report series - Bregvadze, Kakha; Abashishvili, Luka; Tatishvili, Nana Nino; Shatirishvili, Teona; Bedoshvili, Ana; Chikvinidze, Gocha; Rolfs, Arndt; Skrahina, Volha; Tkemaladze, Tinatin (Frontiers in Genetics, 2024)
Spinal muscular atrophy (SMA) is a progressive neuromuscular disorder caused by mutations in SMN1, with disease severity influenced by the number of SMN2 copies. Although SMA is one of the most common autosomal recessive disorders, molecular diagnosis still presents challenges. We present a case series illustrating the variable clinical presentations and diagnostic complexities of spinal muscular atrophy (SMA). Case 1 highlights the importance of multiplex ligation-dependent probe amplification (MLPA) and sequencing for detecting heterozygous deletions and novel variants. Case 2 highlights the limitations of neonatal screening, in which a heterozygous deletion was overlooked. Case 3 demonstrates the need for thorough clinical examination and relevant genetic testing in patients with dual diagnoses, in this case Down syndrome and SMA. In cases 4, 5, and 6, the pseudodominant inheritance pattern is examined in a familial context, highlighting the need for thorough genetic analysis. The presented case series emphasizes the diagnostic challenges and the crucial role of various molecular techniques in the accurate diagnosis and management of SMA.